Determination of Brand Loyalty in Telecommunication Industry: a Literatur Review - ., Ikramuddin; Adam, Muhammad; Sofyan, Hizir; ., Faisal (International Journal of Engineering and Technology, 2018)
This study focuses on the concept of "brand loyalty". The concept of brand loyalty is an important issue in the telecommunication industry and is one of the strategies in relationship marketing. This paper reevaluates the comprehensive determinants of brand loyalty, by testing the model proposed in previous research as a determinant of brand loyalty. The determinants of brand loyalty are service quality, customer satisfaction and brand trust. Several previous studies have addressed the relationship between service quality, customer satisfaction, and brand trust with brand loyalty and the study also presents various current research shortcomings and trends for future studies in the telecommunications industry.Â Â